Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1088/0953-8984/3/51/002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-field spectra of trivalent holmium in HoVO4, HoAsO4, HoPO4and Y(OH)3in the infrared region

Abstract: The polarized absorption spectraof Ho3+ in HoVOr, HoAsOr, Hop04 and(Hoo,l,Yo,s)(OH)a werestudiedin therangefmm5OOOto12000cm-'. Nearly all crystal-field components were found and their crystal quantum numbers P. Y and S could be assigned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…In a previous investigation of the multiplet we carried out a fit of the crystal-field parameters (Bischoff et al 1991) and we found that the experimental results generally could be well reproduced. Indeed, crystal-field calculations were used to analyse the complicated spectra taken at high temperatures.…”
Section: Crystal-field Calculationmentioning
confidence: 83%
See 1 more Smart Citation
“…In a previous investigation of the multiplet we carried out a fit of the crystal-field parameters (Bischoff et al 1991) and we found that the experimental results generally could be well reproduced. Indeed, crystal-field calculations were used to analyse the complicated spectra taken at high temperatures.…”
Section: Crystal-field Calculationmentioning
confidence: 83%
“…In an earlier investigation we determined the crystal-field splittings of nearly all the terms, up to 27600 cm-], of Ho3+ in HoV04, HoAs04, Hop04 and (Ho0.1, Yo.s)(OH)3 (Bischoff er al 1991, Enderle et a! 1990b,c,a, Pilawa 1990.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds with R = rare earth and X = P, As, Cr, and V typically adopt the zircon or monazitetype structure at an ambient condition and change to the scheelite-type polymorph at the high pressures and moderate temperatures [5][6][7][8]. In addition to the structural instabilities, these series of compounds attract the community for their intriguing magnetic [9][10][11] and optical properties [12][13][14]. Over the last few decades, interesting magnetic properties have been realized for RVO 4 [15][16][17][18][19][20][21] and RCrO 4 [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, Malinowski et al point out that Ho 3+ systems have been investigated for application as infrared lasers for remote sensing and medical purposes. Extensive investigations of the optical spectra of Ho 3+ and the subsequent data fitting by crystal field theory have been carried out for HoXO 4 (X = V, P, As), Na 3 [Ho(C 4 H 4 O 5 ) 3 ]·2NaClO 4 ·6H 2 O, M 3 Al 5 O 12 :Ho 3+ (M = Y, Lu), Y 3 Sc 2 Ga 3 O 12 :Ho 3+ , CsCdBr 3 :Ho 3+ , MLiF 4 :Ho 3+ (M = Gd, Y, Lu), Sr 5 (PO 4 ) 3 F:Ho 3+ , KGd(WO 4 ) 2 :Ho 3+ , MBi(XO 4 ) 2 :Ho 3+ (M = Li, Na; X = W, Mo), HoOCl, MF 2 :Ho 3+ (M = Ca, Sr), and Bi 2 TeO 5 :Ho 3+ . Some of these studies have also concerned magnetic properties and optical intensity calculations. ,,, The number of crystal field parameters (CFPs) employed was between 5 , and 14. ,, The fitting parameter values were not always included, but a fairly wide range is apparent from the studies where these were given.…”
Section: Introductionmentioning
confidence: 99%
“…However, Malinowski et al 1 point out that Ho 3þ systems have been investigated for application as infrared lasers for remote sensing and medical purposes. Extensive investigations of the optical spectra of Ho 3þ and the subsequent data fitting by crystal field theory have been carried out for HoXO 4 (X = V, P, As), [2][3][4] Ho 3þ , 7 CsCdBr 3 :Ho 3þ , 8 MLiF 4 :Ho 3þ (M = Gd, Y, Lu), 9 Sr 5 (PO 4 ) 3 F:Ho 3þ , 10 KGd(WO 4 ) 2 :Ho 3þ , 11 MBi(XO 4 ) 2 :Ho 3þ (M = Li, Na; X = W, Mo), 12 HoOCl, 13 MF 2 :Ho 3þ (M = Ca, Sr), 14 and Bi 2 TeO 5 :Ho 3þ . 15 Some of these studies have also concerned magnetic properties 4 and optical intensity calculations.…”
Section: ' Introductionmentioning
confidence: 99%